Makna dan pengalaman kerjasama daripada perspektif kontraktor pembinaan kelas A Melayu di Lembah Klang - Tompang, Lambak; Othman, Jamilah; Idris, Khairuddin; Ismail, Maimunah (Universiti Putra Malaysia Press, 2008)
The study sought to understand the meaning of cooperation by the class A Malay construction contractors and how phenomenon of cooperation takes place. As such, this study explains the meaning and the experience of cooperation based on the practice of selected class A Malay construction contractors in Klang Valley. Phenomenology was used to understand and uncover the cooperation experiences in the career of these class A Malay construction contractors. The narators in this study were class A Malay construction contractors who volunteered to participate and were willing to share their experiences. They have been involved in the business between 15 to 25 years as construction contractors. Criteria based purposive sampling was used to select narators. An open conversation technique was carried out to garner data. The open conversation was tape-recorded and transcribed verbatim. Analysis began as soon as the data were collected. This study assumed that the class A Malay construction contractors experienced cooperation as they undertook the day-to-day activities in running their business. The experiences of the narators revealed that there were several themes, which described the phenomenon of cooperation. A detailed analysis was carried out to identify the themes and categories in order to answer the research questions. These themes were categorized into (i) the meaning of cooperation, (ii) reasons for cooperation, (iii) enhancing cooperation, and (iv) forms of cooperation. Basically, there were several significant meanings of cooperation in the light of a contractor’s task. The study showed that the meanings of cooperation were perceived as working together, partnership, and group work. These three meanings were intertwined and present in all aspects of construction contractors. In addition, the study revealed the sources of cooperation which included aspects of awareness and realization, cultural practice and principles, survival, and competition. In fact, the study identified four elements that enhanced cooperation among the contractors, which were understanding, sincerity, compatibility and experience, and good relationship.Cooperation experienced by the narators was inclusive, that is, it involved all parties concerned in completing a given task. The concerned parties included financial institutions, contractors and construction material suppliers. The cooperation among the contractors was not formal. It was more like a mutual understanding and trust to see the success of certain projects. It could be concluded that the experience of cooperation among the class A Malay construction contractors, was a significant meaning and values within the culture and the Malay individuals themselves which had been rooted for centuries. In fact, the cooperation did not only benefit other members in the business, but also was in a form of an agreement that cooperation was seen as the best formula for those who wanted to lead a conducive, harmonious, peaceful and happy life. This research suggests that continuous and concrete efforts need to be taken to enhance the values of cooperation which are diminishing. They are also encouraged to inculcate the value of cooperation among their business partners.